The Impact of Artificial Intelligent in Education toward 21st Century Skills: A Literature Review - Trisnawati, Winda; Putra, Randi Eka; Balti, Levandra (PPSDP International Journal of Education, 2023)
This study aims to identify the impact of Artificial Intelligent in Education (AIED) toward 21st century skills. The method was a literature review. The research question was “What is the impact of artificial intelligent in education toward 21st century skills?”. The selection and categorization of literature were carried out in the following procedures. The academic databases used to collect papers were Science Direct, Scopus, and Google Scholar. ("artificial intelligence" OR "AI" OR "AIED") AND ("21st century skills" OR "6C"). The time period under review was mainly from 2013 to 2023. It used MAXDQA for thematic analysis. The result shows that artificial intelligent in education have impact toward 21st century skills (6C); character, citizenship, critical thinking, creativity, collaboration, and communication. Various educational and learning issues are addressed using AI techniques. Learning is supported by AI, and students collaborate with AI. By collaborating students and AI, it gives the positive and negative impact toward students’ 21st century skills. the impact of AIED is indeed able to facilitate students’ problems in learning while the ability of students in critical thinking, creative thinking, and character will decrease.